REGULATORY AND LEGAL FRAMEWORK FOR ECONOMIC SECURITY OF TRANSPORT ENTERPRISES IN UKRAINE: SYSTEMATIC ANALYSIS AND IMPROVEMENT DIRECTIONS (Економічний дискурс, 2025)
Introduction. The current stage of Ukrainian economy development is characterized by the growing role of the transport industry as a strategically important sector ensuring the functioning of the national economy and Ukraine’s integration into global economic processes. In the context of globalization, technological progress, and geopolitical changes, the issue of economic security of transport enterprises becomes particularly relevant. Modern challenges require the state to form an effective system of regulatory and legal regulation capable of ensuring the stability and competitiveness of the transport industry. Methods. The research is based on a comprehensive methodological approach combining several complementary methods of scientific cognition. The foundation consists of systematic analysis, comparative-legal method for analyzing sectoral laws on different types of transport, structural-functional analysis to study the functional purpose of each element of regulatory framework, content analysis method for systematizing legislative provisions, and synthesis method for generalizing results. Results. The analysis revealed eight basic instruments of regulatory and legal support for economic security of transport enterprises: licensing system, mandatory insurance, tariff regulation, carrier liability, financial requirements, state control and supervision, social obligations, and technical standards. The existing system is characterized by fragmentation and insufficient systematicity, requiring comprehensive reform considering European integration processes and modern industry development trends. Discussion. Promising research directions include developing a comprehensive concept of legal regulation, studying adaptation mechanisms to European standards, analyzing legal aspects of transport digitalization and cybersecurity, and investigating legal mechanisms for ensuring economic security under martial law conditions.